2020
DOI: 10.1093/fqsafe/fyaa017
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gamma irradiation and storage on the physicochemical properties of tomato fruits in Ghana

Abstract: Objectives Tomato is a popular fruit that makes significant contributions to human nutrition for its content of sugars, acids, vitamins, minerals, lycopene, and other constituents. The fruit, however, has a short shelf life due to its climacteric nature. In view of this, an experiment was conducted to determine the effect of postharvest treatment on the physicochemical properties of fresh tomato fruits. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…For titratable acidity, 10 mL of juice from each treatment was diluted in 50 mL distilled water, and titratable acidity was determined at an endpoint of pH 8.1 with 0.1 N sodium hydroxide (NaOH). The mean titratable acidity was expressed in citric acid percentage [1]. The elemental composition of the fruits was determined at the Nova Scotia Department of Agriculture Laboratory Services, Truro, using inductively coupled plasma mass spectrometry (PerkinElmer 2100DV, Wellesley, Massachusetts, USA) [51].…”
Section: Fruit Quality and Phytochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For titratable acidity, 10 mL of juice from each treatment was diluted in 50 mL distilled water, and titratable acidity was determined at an endpoint of pH 8.1 with 0.1 N sodium hydroxide (NaOH). The mean titratable acidity was expressed in citric acid percentage [1]. The elemental composition of the fruits was determined at the Nova Scotia Department of Agriculture Laboratory Services, Truro, using inductively coupled plasma mass spectrometry (PerkinElmer 2100DV, Wellesley, Massachusetts, USA) [51].…”
Section: Fruit Quality and Phytochemical Analysismentioning
confidence: 99%
“…Tomato (Solanum lycopersicum) is among the most cultivated greenhouse vegetable crops worldwide [1], and is known to be a rich source of health-promoting phytochemicals including carotenoids, phenolics, flavonoids, and ascorbic acid [2]. These phytochemicals exhibit antioxidant properties, which protect cells against oxidative stress by scavenging reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%
“…Also the difference in Bragg irradiated seeds was higher than control as compared to DS-74 seeds. Gyimah et al (2020) showed decrease in moisture content on exposure to gamma irradiation in tomato fruits.…”
Section: Resultsmentioning
confidence: 93%
“…The heat loss because of environmental factors may cause increased evaporation of water. Under ambient room temperature, the non‐irradiated samples exhibited increased softness because of the high respiration rate and increased climacteric activities (Gyimah et al, 2020). In a study by Golding et al (2014), the effects of gamma irradiation at low doses on the quality, proximate, or nutritional profile of “ Brigitta ” blueberry and “ Maravilla ” raspberry fruits were evaluated and authors concluded that 0.15, 0.5, and 0.9 kGy doses did not exert any significant influence on the fruit quality of raspberry or blueberry fruits and there was no interaction effect was observed of storage interval and irradiation treatment on both raspberry and blueberry fruits.…”
Section: Resultsmentioning
confidence: 99%